Moths in Your Pocket : A Guide to the Saturn and Sphinx Moths of the Upper Midwest - Durbin, Jim (Book collections on Project MUSE., 2015)
This welcome addition to Iowa's popular series of laminated guides-the twenty-seventh in the series-illustrates fifty-one species commonly found in the Upper Midwest states of Illinois, Iowa, Indiana, Michigan, Minnesota, Ohio, and Wisconsin. The Saturniid, or Giant Silk moths, are well named. Their large size-up to 6.5 inches for the cecropia moth-and the soft silky browns, greens, and oranges of their wings are unforgettable when they appear at a lighted window at night. Equally well named are the Sphinx or Hawk moths, important pollinators that hover like hummingbirds when necta.